PERMO-CARBONIFEROUS EXTENSION-RELATED MAGMATISM AT THE SW MARGIN OF THE FENNOSCANDIAN SHIELD - Obst K.; Solyom Z.; Johansson L. (My University, 2004)
Permo-Carboniferous rifting in Europe was accompanied by the widespread emplacement of mantle-derived magmas forming regional dyke swarms and sills in northern England, Scotland, Norway and southern Sweden during the late Stephanian and early Autunian. The trends of the dyke swarms intersect at a focal point in the Kattegat south of the Oslo Graben, and are probably all related to a single magmatic centre that could be plume-related. The WNW- to NW-trending dyke swarm at the SW margin of the Fennoscandian Shield in southern Sweden is composed mainly of tholeiitic dolerites, with lesser amounts of alkaline mafic rocks (camptonites, alkali basalts and spessartites) and trachytes. The alkaline mafic rocks are enriched in Ba, Sr, Nb, P and CO2, implying a metasomatic enrichment of their upper-mantle source prior to melting. After generation of alkaline melts by relatively small degrees of partial melting, increased extension was accompanied by the formation of subalkaline tholeiitic magmas. Whole-rock compositions (Mg-numbers between 55 and 30) and mineral chemistry (olivine Fo60-Fo40; clinopyroxene approximately Wo30En45Fs15; plagioclase An70-An50) indicate relatively evolved melts that have undergone crystal fractionation of olivine and clinopyroxene. Two groups of dolerites can be distinguished on the basis of bivariate element plots, e.g. Zr-TiO2 and La-Sm. Although both groups show enrichment in the whole range of incompatible trace elements, slight differences in mantle-normalized trace-element patterns and different Nb/La ratios suggest that they were generated from two different sources. Group I dolerites were formed from a (re-)enriched, but isotopically mildly depleted, sublithospheric garnet-bearing mantle source (Nb/La mostly > 0.9, εNdi = + 4 to + 3, where εNdi is the initial Nd isotope ratio), whereas group II dolerites seem to indicate mixing of the asthenospheric-derived magmas with lithospheric mantle melts (Nb/La mostly < 0.9, εNdi = 0 to - 1). Increasing Th/Ta ratios together with decreasing U/Nb ratios from group I towards group II dolerites further reflect progressive crustal contamination.)
Keywords: Carboniferous; Paleozoic::Carboniferous; Палеозой::Пермская; Paleozoic::Permian; Палеозой::Каменноугольная